Good riddance to bad government? Institutional performance voting in Swedish municipalities. (27th March 2022) - Broms, Rasmus
Abstract: Electoral accountability is widely considered to be an essential component for maintaining the quality of a polity's institutions. Nevertheless, a growing body of research has found weak or limited support for the notion that voters punish political corruption, a central but partial aspect of institutional quality. In order to capture the full range of institutional dysfunction an electorate should be incentivised to punish, I further the concept of institutional performance voting, that is, voting on institutional quality as a whole. Using a novel data set on performance audit reports in Swedish municipalities between 2003 and 2014, I find that audit critique is associated with a statistically significant but substantively moderate electoral loss of about a percentage point for mayoral parties, while simultaneously associated with a 14 percentage point decrease in their probability of reelection.